Book reviews: Claudia Baicu, Banking and international trade finance - Negruş, Mariana (Annals of Spiru Haret University. Economic Series, 2010)
Since the latest issue of the book, the financial and banking world has undergone significant changes that culminated with the global financial crisis. This new background requires the rethinking of some concepts and practices, regulations and strategies at national or international level, aspects taken into account by the author in elaborating the second issue. In this respect, the chapters on improved regulation and supervision of international banking, new payment techniques in the context of implementing the electronic payment system, new approaches in guarantees field, are eloquent